"Tingkatkan Kualitas Pendidikan: Peran Materi MIPA dalam Mencapai Tujuan Pendidikan Nasional" - Siti Nur Maulidah; Zahrah Nazhifah Iftinany; Reisa Evita Zahradia; Ikmawati Ikmawati; Kurniawan Kurniawan (Populer: Jurnal Penelitian Mahasiswa, 2024)
Mathematics and Natural Sciences (MIPA) education has a very important role in shaping a smart, creative and innovative generation, in line with Indonesia's national education goals. This article explores the contribution of MIPA in improving the quality of education in Indonesia, especially through the development of critical and analytical thinking skills. This research uses a literature study method with a qualitative descriptive approach, and is supported by interviews with teachers in East Kalimantan. The results showed that MIPA learning can help learners develop scientific skills and form positive characters such as honesty, consistency and logical thinking. In addition, teachers, principals and parents have a crucial role in supporting the improvement of education quality. With the synergy of various parties, the integration of MIPA materials is expected to realize the goals of national education, namely creating a society that is intelligent, noble, and ready to face global challenges.